The Effect of Algal-Gardening Damselfish on the Resilience of the Mesoamerican Reef - Randazzo Eisemann, Ángela; Montero Muñoz, Jorge Luis; McField, Melanie; Myton, Jenny; Arias-González, Jesús Ernesto (Frontiers in Marine Science, 2019)
The structures, functions, and services provided by coral reef ecosystems are deteriorating worldwide. However, not all coral reefs are affected the same way, with some showing signs of resistance and/or recovery from disturbances. Understanding the drivers and feedbacks that contribute to shifts in community structure is valuable to support resilience-based management. In this study, key community variables that influence the resilience of coral reef ecosystems were examined in 64 sites of the Mesoamerican Reef (MAR) monitored in both 2006 and 2016, as part of the Healthy Reef Initiative (HRI), using the Atlantic and Gulf Rapid Reef Assessment (AGRRA) monitoring protocol. Based on benthic cover thresholds, sites were classified into three different states: coral state (CS) with >10% live coral and <5% fleshy macroalgae; stressed coral state (SCS) with >10% live coral and >5% fleshy macroalgae and; depauperate coral state (DCS) <10% live coral. The associations between site states and the density of different fish functional groups were analyzed to determine their effects on coral reef resilience. The results highlight that territorial herbivores (algal-gardening damselfish) may play a key role in maintaining positive feedbacks towards macroalgae-stressed states. This supports the recommendation of reinforcing Marine Replenishment Zones (MRZ) in order to promote healthy populations of resident predator fish (like groupers and snappers), which could potentially regulate algal-gardening damselfish populations and diminish negative cascade effects on coral reefs. Collaborative and resilience-based management will continue to be promoted by the HRI partners, supporting the establishment of additional MRZs along with ongoing efforts to directly protect herbivorous fish (surgeonfish and parrotfish) and to improve water quality, through better wastewater treatment, watershed management and coastal development plans, with the purpose of continuing to build coral reef resilience in the MAR.